Prevalence of isolated gastrocnemius tightness in patients with foot and ankle pathology: a population-based study. (July 2018) - Malhotra, K.; Chan, O.; Cullen, S.; Welck, M.; Goldberg, A. J.; Cullen, N.; Singh, D.
Abstract : Aims: Gastrocnemius tightness predisposes to musculoskeletal pathology and may require surgical treatment. However, it is not clear what proportion of patients with foot and ankle pathology have clinically significant gastrocnemius tightness. The aim of this study was to compare the prevalence and degree of gastrocnemius tightness in a control group of patients with a group of patients with foot and ankle pathology. Patients and Methods: This prospective, case-matched, observational study compared gastrocnemius tightness, as assessed by the lunge test, in a control group and a group with foot and ankle pathology. Gastrocnemius tightness was calculated as the difference in dorsiflexion of the ankle with the knee extended and flexed. Results: A total of 291 controls were paired with 97 patients with foot and ankle pathology (FAP). The mean gastrocnemius tightness was 6.0° (sd 3.5) in controls and 8.0° (sd 5.7) in the FAP group (p < 0.001). Subgroup analysis showed a mean gastrocnemius tightness of 10.3° (sd  6.0) in patients with forefoot pathology versus 6.9° (sd 5.3) in patients with other pathology (p = 0.008). A total of 12 patients (37.5%) with forefoot pathology had gastrocnemius tightness of > two standard deviations of the control group (> 13°). Conclusion: Gastrocnemius tightness of > 13° may be considered abnormal. Most patients with foot and ankle pathology do not have abnormal degrees of gastrocnemius tightness compared with controls, but it is present in over a third of patients with forefoot pathology. Cite this article: Bone Joint J 2018;100-B:945–52.